Otomasi Alat Pemilah Sampah Menggunakan Algoritma Yolo dengan Pendekatan Quality Function Deployment (QFD) Guna Mengurangi Residu Sampah di TPS 3R Tenggilis - Awang, Taufiq Labdo Ganiyu; Nuha, Hilyatun; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The TPS Reduce, Reuse and Recycle Tenggilis Mejoyo faces a problem with waste residue levels of 58.61%, far above the ideal target of 30%. This research develops an automated waste sorting device using the Quality Function Deployment (QFD) approach to optimize the sorting process. The research methodology employs four QFD phases from Voice of Customer to production planning. A prototype measuring 40x10 cm with a conveyor speed of 10 cm/s was developed based on high-priority technical responses. Testing was conducted with 5 repetitions using 150 mixed samples of plastic and paper. Results showed an overall accuracy of 83.95% with details of 85.3% for plastic and 82.6% for paper/cardboard. Actual capacity reached 13 sorts/minute for plastic and 21 sorts/minute for paper. Implementation of the device increased accuracy from 65% to 84% (19% improvement). The automation system with YOLO algorithm proved effective in improving sorting effectiveness and contributing to waste residue reduction at the 3R TPS.